2017
DOI: 10.3390/ijerph14090981
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Child Behavioral Problems: The Mediating Role of Parenting and Parental Well-Being

Abstract: The detrimental impact of poverty on child behavioral problems is well-established, but the mechanisms that explain this relationship are less well-known. Using data from the Families in Germany Study on parents and their children at ages 9–10 (middle childhood), this study extends previous research by examining whether or not and to what extent different parenting styles and parents’ subjective well-being explain the relationship between poverty and child behavior problems. The results show that certain paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 30 publications
5
36
0
4
Order By: Relevance
“…The association of material deprivation and financial stress with children's behavior problems even in the absence of income poverty is consistent with prior research (Gershoff et al 2007;Lee and Lee 2016;Leininger and Kalil 2014;Ponnet 2014;Zilanawala and Pilkauskas 2012). The effect sizes, which ranged from 0.06 SD and 0.25 SD, depending on the specific economic hardship combination and the type of behavior problems, are relatively consistent with prior research on the effects of income poverty on children's mental health and behavior problems (Costello et al 2003;Kaiser et al 2017;McLeod and Shanahan 1993). While we found that all economic hardship combinations were associated with higher levels of children's behavior problems, the combination of material deprivation and subjective financial stress and the combination of all three dimensions of economic hardship were associated with the highest levels of behavior problems.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The association of material deprivation and financial stress with children's behavior problems even in the absence of income poverty is consistent with prior research (Gershoff et al 2007;Lee and Lee 2016;Leininger and Kalil 2014;Ponnet 2014;Zilanawala and Pilkauskas 2012). The effect sizes, which ranged from 0.06 SD and 0.25 SD, depending on the specific economic hardship combination and the type of behavior problems, are relatively consistent with prior research on the effects of income poverty on children's mental health and behavior problems (Costello et al 2003;Kaiser et al 2017;McLeod and Shanahan 1993). While we found that all economic hardship combinations were associated with higher levels of children's behavior problems, the combination of material deprivation and subjective financial stress and the combination of all three dimensions of economic hardship were associated with the highest levels of behavior problems.…”
Section: Discussionsupporting
confidence: 85%
“…Though there is a considerable body of literature showing the negative effects of economic hardship on children, this extant empirical literature also does not reflect the growing evidence that the three dimensions of economic hardship are distinct. Many of the studies that have found a significant association between income poverty and children's behavior problems did not account for either material deprivation or subjective financial stress (Costello et al 2003;Dearing et al 2006;Kaiser et al 2017;Lansford et al 2018;McLeod and Shanahan 1993). Those studies that specifically tested the FSM did account for material deprivation and subjective financial stress, but only as mediators, finding a significant association between income poverty and children's behavior problems mediated by economic strain (i.e., material deprivation and subjective financial stress) (Conger and Conger 2002;Conger et al 1992;McLoyd 1990;Mistry et al 2008).…”
Section: Prior Empirical Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, sedentary time and MVPA were assessed objectively, and analyses were adjusted for known confounding factors including poverty which is a predisposing factor to BMI and SEW difficulties [39]. The limitations of the study should also be recognised.…”
Section: Discussionmentioning
confidence: 99%